DAMPAK KOMUNIKASI E-WOM TERHADAP NIAT BERKUNJUNG DENGAN CITRA DESTINASI SEBAGAI VARIABEL MEDIASI (STUDI PADA FESTIVAL TELUK JAILOLO KABUPATEN HALMAHERA BARAT) - Agung, Muhammad; Hidayanti, Ida; Hi. Yusuf, Ibnu Sina (Jurnal MS, 2022)
Objective: The development of information and communication technology that is developing rapidly can be utilized as a means to introduce Indonesian tourism. One way that can be done is to stimulate electronic word of mouth communication between tourists through social media Instagram, Facebook and Twitter. This study aim s to determine and analyze the effect of Electronic Word of Mouth Communication on the Visiting Intentions mediated by the Destination Imagery at the Jailolo Bay Festival. This research is planned to be carried out in October-December 2019. Methodology: The analytical model used are path analysis as tools for the statistical test. Data collection tools used are questionnaires and interviews, and the number of respondents was 95 respondent. Finding: H1, H2, H3, and H4 are accepted, at the 5% confidence level. Conclusion: The results of this study are that electronic word of mouth has a positive effect on destination image and visiting intentions. This means that the more electronic word of mouth communication on Jailolo Bay Festival social media, the better the popularity of the tourist destination will increase in the community. Likewise, social media users are more interested if they see information and reviews presented through social accounts about the state of an activity at the Jailolo Bay Festival. Furthermore, the destination image also has a positive effect on intention. That is, the better the image of a destination at the Jailolo Bay Festival will influence people to visit the activity. And from Electronic word of mouth with the intention to visit mediated by the image of destinas obtained a positive effect. This means that if the information provided through social media with a good opinion, in the form of a positive image of the Jailolo Bay Festival activities will increase the intention to visit tourists.